Regulation of Adult CNS Axonal Regeneration by the Post-transcriptional Regulator Cpeb1 - Lou, Wilson Pak-Kin; Mateos, Alvaro; Koch, Marta; Klussman, Stefan; Yang, Chao; Lu, Na; Kumar, Sachin; Limpert, Stefanie; Göpferich, Manuel; Zschaetzsch, Marlen; Sliwinski, Christopher; Kenzelmann, Marc; et al. (Frontiers in Molecular Neuroscience, 2018)
Adult mammalian CNS neurons are unable to regenerate following axonal injury, leading to permanent functional impairments. Yet, the reasons underlying this regeneration failure are not fully understood. Here, we study the transcriptome and translatome shortly after spinal cord injury. Profiling of the total and ribosome-bound RNA in injured and naïve spinal cords identify a substantial post-transcriptional regulation of gene expression. In particular, transcripts associated with nervous system development were down-regulated in the total RNA fraction while remaining stably loaded onto ribosomes. Interestingly, motif association analysis of post-transcriptionally regulated transcripts identified the cytoplasmic polyadenylation element (CPE) as enriched in a subset of these transcripts that was more resistant to injury-induced reduction at transcriptome level. Modulation of these transcripts by overexpression of the CPE binding protein, Cpeb1, in mouse and Drosophila CNS neurons promoted axonal regeneration following injury. Our study uncovers a global evolutionarily conserved post-transcriptional mechanism enhancing regeneration of injured CNS axons.